2021
DOI: 10.1186/s12935-021-01865-4
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of angiopoietin-like 4 slows ovarian cancer progression through vascular endothelial growth factor receptor 2 phosphorylation

Abstract: Background As a tissue-specific proangiogenic or antiangiogenic agent, angiopoietin-like 4 (ANGPTL4) has recently gained attention in many diseases, such as metabolic syndrome, cardiovascular disease and cancer. However, the roles of ANGPTL4 in angiogenesis and tumor growth in epithelial ovarian cancer, the most lethal gynecologic malignancy, remain unclear. Objective To identify a novel mechanism of ANGPTL4 inhibition in epithelial ovarian cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Consistent with other studies [ 23 26 ], we observed that ANGPTL4, PYGB and IRS2 were highly expressed in ovarian tumor tissues and patients with high expression of ANGPTL4, PYGB or IRS2 had significantly lower OS rates than patients with low expression of these factors. ANGPTL4, a secreted glycoprotein in the angiopoietin-like protein family, is involved in glucose and lipid metabolism and also plays an essential role in the prevention of apoptosis, induction of angiogenesis, inhibition of angiogenesis and facilitation of metastasis [ 23 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with other studies [ 23 26 ], we observed that ANGPTL4, PYGB and IRS2 were highly expressed in ovarian tumor tissues and patients with high expression of ANGPTL4, PYGB or IRS2 had significantly lower OS rates than patients with low expression of these factors. ANGPTL4, a secreted glycoprotein in the angiopoietin-like protein family, is involved in glucose and lipid metabolism and also plays an essential role in the prevention of apoptosis, induction of angiogenesis, inhibition of angiogenesis and facilitation of metastasis [ 23 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…ANGPTL4, PYGB and IRS2 have been reported to be upregulated in OC, and this dysregulation promotes OC cell proliferation, invasion, migration and drug resistance [ 23 26 ]. However, the expression and function of ISG20 and SEH1L in OC have not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ANGPTL4 is activated by hypoxia-inducible factor-1α (HIF-1α) and confers protection against hypoxiainduced apoptosis [34]. It is demonstrated that ANGPTL4 is overexpressed in OC and related to shorter relapse-free survival times in serous OC [35][36][37]. In addition, ANGPTL4 is significantly related to the poor prognosis of patients with non-small-cell lung cancer, lung adenocarcinoma, and cervical cancer [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that angiopoietin-like protein (ANGPTL) is associated with apoptosis, inflammation, tumor development, and metabolism [ 16 19 ]. Previous studies have illustrated that increased expression of Angptl4 in synovial fibroblasts within arthritic tissues [ 20 ] and angiopoietin family proteins contributes to the pathogenesis of OA [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%